Developmental periods of choline sensitivity provide an ontogenetic mechanism for regulating memory capacity and age-related dementia - Meck, Warren H.; Williams, Christina L.; Cermak, Jennifer M.; Blusztajn, Jan K. (Frontiers in Integrative Neuroscience, 2008)
In order to determine brain and behavioral sensitivity of nutrients that may serve as inductive signals during early development, we altered choline availability to rats during 7 time frames spanning embryonic day (ED) 6 through postnatal day (PD) 75 and examined spatial memory ability in the perinatally-treated adults. Two sensitive periods were identified, ED 12-17 and PD 16-30, during which choline supplementation facilitated spatial memory and produced increases in dendritic spine density in CA1 and dentate gyrus (DG) regions of the hippocampus while also changing the dendritic fields of DG granule cells. Moreover, choline supplementation during ED 12-17 only, prevented the memory decline normally observed in aged rats. These behavioral changes were strongly correlated with the acetylcholine (ACh) content of hippocampal slices following stimulated release. Our data demonstrate that the availability of choline during critical periods of brain development influences cognitive performance in adulthood and old age, and emphasize the importance of perinatal nutrition for successful cognitive aging.